Pasażerowie w tajnym języku personelu pokładowego - Kopecka, Beata Marta (Acta Neophilologica, 2020)
This article is devoted to the linguistic analysis of terms referring to air passengers in the language of flight attendants. The term secret language denotes a subsection of the aviation slang used by cabin crews to communicate information meant not to be understood by passengers. The analysis, aiming at discovering the motivation for the creation of such terms, focuses on the role of metaphor and metonymy. Metaphor and metonymy are treated in accordance with the assumptions of cognitive linguistics.